On the Dynamics of the Recursive Sequence - Mehmet Gümüş; Özkan Öcalan; Nilüfer B. Felah (Discrete Dynamics in Nature and Society)
We investigate the boundedness character, the oscillatory, and the periodic character of positive solutions of the difference equation , where , , and the initial conditions are arbitrary positive numbers. We investigate the boundedness character for . Also, we investigate the existence of a prime two periodic solution for is odd. Moreover, when is even, we prove that there are no prime two periodic solutions of the equation above.